Middle- / long-distance runners` functionality test in daily middle altitude trainings - Shlyk, N. I.; Alabuzhev, A. E.; Nikolaev, Y. S. (Theory and Practice of Physical Culture, 2018)
The article analyzes the cardiac activity regulation and variations based on the middle-/ long-distance runners` heart rate variability (HRV) data in the middle altitude training process, with a special emphasis on their exposure to fatigue and overtraining due to the training process mismanagement, inadequate customization to the individual capacities and/or untimely health rating tests and examinations. It was found by the study that the daily HRV tests of runners in the middle altitude trainings give the means to find, on a timely basis, the individual limits of the bodily resources and regulatory mechanisms that shall in no case be surpassed otherwise the trainees may be exposed to risks of regulatory deficiencies, overtraining and cardiac function disorders. It was also found that most of the athletes arrive to the middle altitude training camps without prior medical examinations. The HRV data and analyses showed that the challenging altitude acclimatization in the first training week with two training sessions per day is often detrimental to adaptability, resource mobilization, autonomic balancing and autonomic response mechanisms with the associating health disorders and, hence, excessive fatigue and overtraining by the end of the altitude training cycle. The issues related to the cardiac function regulation mechanism in the twice-per-day running trainings and the relevant health disorders are still largely underexplored and need to be duly addressed by the sport science.